2017
DOI: 10.1021/acssensors.7b00304
|View full text |Cite
|
Sign up to set email alerts
|

MOFs for the Sensitive Detection of Ammonia: Deployment of fcu-MOF Thin Films as Effective Chemical Capacitive Sensors

Abstract: This work reports on the fabrication and deployment of a select metal-organic framework (MOF) thin film as an advanced chemical capacitive sensor for the sensing/detection of ammonia (NH) at room temperature. Namely, the MOF thin film sensing layer consists of a rare-earth (RE) MOF (RE-fcu-MOF) deposited on a capacitive interdigitated electrode (IDE). Purposely, the chemically stable naphthalene-based RE-fcu-MOF (NDC-Y-fcu-MOF) was elected and prepared/arranged as a thin film on a prefunctionalized capacitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(128 citation statements)
references
References 60 publications
1
127
0
Order By: Relevance
“…However, at 40 °C, the gas responses of MOF 1 to 2 ppm NH 3 gas are 61, 2, and 10 % at 68, 85, and 98 % RH, respectively. In general, the sensor shows excellent sensitivity at room temperature and 68 % RH, which is among the highest of the reported room‐temperature sensors under 60 % RH and other RHs (Table S3 in the Supporting Information) . What calls for special attention is that the measurement conditions of most of the previous ammonia gas sensors are under dry air or N 2 or very low RH atmosphere; the case under high RH is very rare .…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…However, at 40 °C, the gas responses of MOF 1 to 2 ppm NH 3 gas are 61, 2, and 10 % at 68, 85, and 98 % RH, respectively. In general, the sensor shows excellent sensitivity at room temperature and 68 % RH, which is among the highest of the reported room‐temperature sensors under 60 % RH and other RHs (Table S3 in the Supporting Information) . What calls for special attention is that the measurement conditions of most of the previous ammonia gas sensors are under dry air or N 2 or very low RH atmosphere; the case under high RH is very rare .…”
Section: Resultsmentioning
confidence: 73%
“…However,a t4 08C, the gas responses of MOF 1 to 2ppm NH 3 gas are 61, 2, and 10 %a t6 8, 85, and 98 %R H, respectively.I ng eneral,t he sensor shows excellent sensitivity at room temperature and 68 %RH, which is among the highest of the reported room-temperature sensors under 60 %R H [17] and other RHs ( Table S3 in the Supporting Information). [18,[48][49][50][51][52][53][54][55][56] What calls for special attention is that the measurement conditions of most of the previousa mmonia gas sensors are under dry air or N 2 or very low RH atmosphere; [50][51][52][53][54][55][56] the case under high RH is very rare. [49] This may be because they are based on ad ifferent sensing mechanism,i nw hich the high RH atmosphere can result in inaccurate resultso ri nactivity toward determination.…”
Section: As Shown Inmentioning
confidence: 99%
“…Recently metal-organic frameworks (MOFs), porous materials of a crystalline structure comprising bridged organic ligands and metal centers, have been attracted significant attention in gas sorption average owing to their large pore volumes and surface areas. Several studies have been 1 3 reported on MOFs utilization as heterogeneous catalysts [1][2][3][4], in gas storage [5], separation [6], drug delivery [7], and sensing [8,9]. These materials have been explored because of their intrinsic high surface area, tunable pores, and various functionalities [10].…”
Section: Introductionmentioning
confidence: 99%
“…[5,16,[25][26][27][28] On the other hand, based on the outstanding advantagesofMOFs, the exploration of the practical application of electrically conductive MOFs has received extensive attention, especially in the field of chemoresistive sensors. [29][30][31][32][33][34] Representatively,D incǎ et al demonstrated an array of cross-reactive sensor for the identification of different typeso fv olatile organic compounds (VOCs). [34] Nevertheless, the studies on proton conductingM OFs as sensors are very limited.…”
Section: Introductionmentioning
confidence: 99%